Impact of Profitability, Leverage, Capital Intensity, Firm Size, and Firm Age on Tax Avoidance - Gowira, David; Haryono, Haryono; Dosinta, Nina Febriana (University of Merdeka Malang, 2024)
Indonesia's primary source of state revenue is taxes and is used to support economic growth to achieve the vision of